Pernikahan Adat Dayak Ngaju Perspektif Hukum Islam (Studi di Kabupaten Gunung Mas Kalimantan Tengah) - Surya Sukti; Munib Munib; Imam S Arifin (El-Mashlahah, 2020)
ABSTRACTDayak traditional marriage is a solution for those who have problems doing marriage according to the marriage law, such as underage marriages, interfaith marriages, there are even those who are married in customary ways then they live together and after a long time carry out marriage according to Islamic law. From the findings in the field, there are those who marry according to custom and after having new children marry in Islam. This phenomenon is very interesting to discuss and research, especially from the perspective of Islamic law. The requirement for a Dayak customary marriage is 17 points and this is quite heavy for the bridegroom, so do not enforce it, especially for the less fortunate prospective groom. Considering that many of the traditional Dayak marriages originate from the Hindu Kaharingan religion and some of them are against Islamic law, it is better for those who are married to be Muslim, so when opening the lawang sekepeng drinking tuak is replaced by drinking milk or other halal drinks. If there is a customary law that is against Islamic law, then the customary law should be defeated, such as interfaith marriage and underage marriage as well as traditional marriage and then gather as husband and wife before marriage in Islam.Keywords: Customary Marriage, Dayak Ngaju and Islamic Law.INTISARIPerkawinan adat dayak merupakan solusi bagi yang bermasalah melakukan perkawinan menurut undang-undang perkawinan, seperti nikah di bawah umur, nikah beda agama, bahkan masih ada yang nikah secara adat kemudian mereka hidup berkumpul dan setelah lama baru melaksanakan pernikahan secara syari’at Islam. Dari temuan di lapangan ada yang menikah secara adat dan setelah mempunyai anak baru menikah secara Islam. Fenomena ini sangat menarik untuk dibahas dan diteliti, apalagi ditinjau dari perspektif hukum Islam. Persyaratan pernikahan adat dayak ada 17 poin dan ini cukup berat bagi mempelai laki-laki, oleh sebab itu jangan dipaksakan terutama bagi calon mempelai laki-laki yang kurang mampu. Mengingat pernikahan adat dayak itu banyak bersumber dari agama Hindu Kaharingan dan di antaranya ada yang bertentangan dengan hukum Islam, sebaiknya bagi yang menikah itu beragama muslim maka ketika membuka lawang sekepeng itu minum tuak diganti dengan minum susu atau minuman lainnya yang halal. Jika ada hukum adat yang bertentangan dengan hukum Islam maka sebaiknya hukum adat dikalahkan, seperti nikah beda agama dan nikah di bawah umur serta nikah adat kemudian berkumpul sebagaimana suami isteri sebelum nikah secara Islam.Kata Kunci: Pernikahan Adat, Dayak Ngaju dan Hukum Islam.